The High-Altitude Lab (HAL) and Hypoxia Awareness Training at Embry-Riddle Aeronautical University: What is life really like in thin air? - Wagner, Scott; Bowyer, Samantha; Bates, Jackson; Cadinouche, Ejaaz; Fisher-Smith, Riley; Hayden, Alyssa; Louderback, Courtney; Zappa, Tyler (Experiential Learning and Teaching in Higher Education, 2025)
Embry-Riddle Aeronautical University trains students for stressful settings by recreating the experience of flying through a thin atmosphere, without leaving the ground. Students learn firsthand about the physical and cognitive strains of low oxygen, understanding how to recognize the warning signs in themselves and the people around them before it's too late. These insights come from essentially experiential education -- in ways they can't get from secondhand accounts, or even virtual reality.